Educação e Democracia: Análise Normativa do Processo Eleitoral para o Cargo de Diretor Escolar na Rede Estadual de Educação de Mato Grosso do Sul (1999 a 2018) - Brito, Jéssica da Costa (2021)
This dissertation is part of the research line “History, Politics, Education” of the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul (PPGEdu/FAED/UFMS), having as its object the normative analysis, especially of the which provide for election as provisiono f the position of school diretor of school units of the State Education Network of Mato Grosso do Sul (RRE/MS). The general objective is to analyze the norms of the electoral process for the position of director in the REE/MS schools, between 1999 and 2018. As specific objectives, conceptualize State and democracy from the adopetd referencial; discuss the main forms of provision for selection of the school principal and the nature of this position; and identify the main changes in the regulations regarding the electoral processo of the position of director of REE/MS schools. The guiding question was “what were the main changes in educational regulations between 1999 and 2018 that expressed the disputes surrounding the implementation of elections for principals in school in the State Education Network in the state of Mato Grosso do Sul and the roles played by state aithorities and by the teaching movement in the changes?” To answer it, the mehodology adopetd was bibliographic and documentar research, observing the critical theoretical framework. Therefore, a survey of documents was carried out, mainly state regulations relevant to the object of study, produced by the State Department of Education of Mato Grosso do Sul (SED/MS) and made available on its website, by the Legislative Assembly and Other instances, and bibliographical review about basic concepts in the área of School Managament, in theses, dissertations and scientific articles, in order to guide discussions on Democratic Management, Public Policies and Election of Directors. From the development of the reserach, we noticed significant clashes between representatives of the teaching movement and the Executive Branch, especially during the terms of governos André Puccinelli (2007-2014) and Reinaldo Azambuja (2015-2018). We also found that the normative changes evidenced the private logic in the electoral process, adopting stages with na emphasis on effectiveness, efficiency and meritocracy, demonstrating the contractions in the public-private relationship. These contradictions are exposed in the actions of policial agentes and the State Government in the governments of José Orcírio Miranda dos Santos, André Puccineli and Reinaldo Azambuja, who, at the same time They implemented the election of directors (even if through decrees), showing democratic discourses, does not give in the field of democratic freedoms, nor does it give in to requests from the category of teachers. Key-words: Educationl Policy. Democratic management of Basic Education. Democratic management in Mato Grosso do Sul. Normative analysis. Election of directors.